A durable superhydrophobic surface with protective nest-like micro-containers. (December 2022) - Yang, Sijie; Luo, Song; Yang, Lansong; Yang, Xin
Abstract: The preparation of superhydrophobic surfaces is a promising potential strategy for protecting metal substrates and allowing their utilization in a broader range of applications. Many studies have investigated metal-based superhydrophobic surfaces, and various methods for fabricating these surfaces have been reported. However, the fragility of their structure and composition has long puzzled researchers and hindered the development of superhydrophobic surfaces for practical use. Moreover, nanostructures are notoriously more delicate than microstructures. Therefore, developing surfaces with durable structures at both the nanoscale and microscale is crucial. Herein, a novel method was developed to rapidly prepare many nest-like "micro-containers". Green ingredients were then stored and protected in these nest-like micro-containers as nanostructures and low surface energy components. The approach reported herein allows for the fabrication of a favorable hierarchical structure with a well-protected structure and composition. Characterization and a variety of measurements were performed to confirm that the unique structural design of this superhydrophobic surface produced an ultra-high water contact angle with low adhesion. Furthermore, the superhydrophobic surface exhibited good resistance to mechanical damage, good corrosion resistance, high environmental durability, and self-cleaning properties. Graphical Abstract: ga1 Highlights: A structural protection strategy to fabricate durable superhydrophobic surfaces is proposed. Low surface energy components are stored, protected, and recovered. Preparation methods are green, low-cost and easy to implement. Formation mechanism is analyzed in detail. Excellent durability, anti-corrosion and self-cleaning are performed.